Prospects for the detection of transient neutrino sources with PLEnuM - Schumacher, Lisa; Oikonomou, Foteini (Proceedings of Science, 2024)
The discovery of high-energy astrophysical neutrinos in the TeV-PeV range by IceCube marked the start of neutrino astronomy, and the search for their sources continues. Two promising source candidates have been identified by IceCube: NGC 1068 in the 1 TeV-10 TeV range and TXS 0506+056 in the 0.1-1 PeV range. Both sources have gamma-ray counterparts, but additional time information of both neutrinos and gamma rays were essential for the identification of TXS 0506+056. The Planetary Neutrino Monitoring (PLEnuM) concept is an approach for combining the exposures of all current and future neutrino observatories - such as KM3NeT, Baikal-GVD, P-ONE in the Northern Hemisphere, and IceCube-Gen2 in the Southern Hemisphere. Using this PLEnuM approach, we estimate how the detection capability for transient sources candidates like blazars and GRBs improves once the future neutrino observatories come online. In addition, we present how the combined, instantaneous field of view of PLEnuM improves the real-time detection rate of rare, very-high-energy neutrinos across the entire sky.
CRIS-Team Scopus Importer:2025-02-04